Astrometric observations of asteroids and comets at the Moletai Astronomical Observatory - Cernis, K.; Zdanavicius, J.; Zdanavicius, K. (Известия Крымской астрофизической обсерватории, 2007)
We describe the observational project devoted to astrometric observations of Near-Earth Objects (NEO), main belt asteroids and comets at the Moletai Observatory, Lithuania. Exposures are obtained with the two telescopes of the observatory: 0.35/0.50 m f/3.5 Maksutov telescope and the 1.65 m f/3.1 reflector with a CCD camera. The results of more than 8 800 positions of asteroids and comets have been published in the Minor Planet Circulars and Minor Planet Electronic Circulars. During the 2001−2005 period 121 new main belt asteroids were discovered and a few NEO objects were detected independently.